ROBERT HALL ON PHYSICIAN-ASSISTED SUICIDE AND ITS IMPLICATION FOR MEDICAL ETHICS - Chrisantus Kanayochukwu Ariche; Emmanuel Kelechi Iwuagwu (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The practice of physician-assisted suicide has been a complex and controversial issue in bio-medical ethics. Bioethicists, philosophers, theologians and scholars from different fields continue to make contributions to this age long practice. Contributing to this controversial issue Robert Hall a professor of philosophy in his paper Physician-Assisted Suicide Should be Legalized, argues that such assistance is ethical, humane and should be legalized. This is problematic and worrisome. However, from the Deontologic perspective, this paper argues that such assistance is unethical and not in tandem to medical ethics. Contributing to this discussion this paper further argues that Hall’s view is problematic and if accepted it will definitely turn the physician from a health care giver to a death inducer. This paper adopted the method of textual analysis and it is purely argumentative